2013
DOI: 10.1117/1.oe.52.3.030901
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-optical grating sensors for wind turbine blades: a review

Abstract: Abstract. With the rapid growth of wind turbines and focus on maintenance costs structural measurements are becoming essential. Fiberoptical sensors have physical properties that make them suitable for embedding in wind turbine blades, such as small size and immunity to electrical interferences. Fiber-optical grating sensors can be utilized to provide important information regarding strain, temperature, and curvature of the blades, which can be applied in condition-monitoring to detect fatigue failure and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 69 publications
0
35
0
Order By: Relevance
“…LPGs are sensitive to temperature and strain, which must be taken into consideration for a given application; however, the sensitivity can be suppressed by the fiber and grating composition. 4 For example, considering the D-shaped fiber, the germanium doped core can expand more in one direction compared to a symmetrical fiber affecting the sensitivity to strain and temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LPGs are sensitive to temperature and strain, which must be taken into consideration for a given application; however, the sensitivity can be suppressed by the fiber and grating composition. 4 For example, considering the D-shaped fiber, the germanium doped core can expand more in one direction compared to a symmetrical fiber affecting the sensitivity to strain and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that LPGs are suitable for structural health monitoring, especially for large structures such as wind turbines, as they can provide directional bend sensing of the blades, due to the fiber geometry. 4 These sensors can also provide the possibility for direct compensation of temperature drift. The utilization in D-shaped fibers provides a good access to the surroundings while retaining sufficient robustness; therefore, they are also ideal for several other evanescent field applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chapter is mainly based on the work presented in the publication "Fibre-optical grating sensors for wind turbine blades: a review" [18]. This paper provides review of this field and describes the current status of utilization fibre optical gratings technology as wind turbine blade load sensors.…”
Section: Fibre Gratingsmentioning
confidence: 99%
“…FBGs are local sensors with high sensitivity and reliability, allowing the possibility to multiplex several FBG sensors in a single optical fibre. In recent years, most of the investigations about fibre optic applications have been related to FBGs due to the variety of advantages that they offer (Choi et al 2012;Glavind et al 2013;Kim et al 2013Kim et al , 2014. FBGs are periodic variations in the refractive index of the core of the optical fibre.…”
Section: Fibre Opticsmentioning
confidence: 99%